Why are social enterprises good candidates for social innovation? Looking for personal and institutional drivers of innovation - Tortia, Ermanno C.; Degavre, Florence; Poledrini, Simone (Annals of Public and Cooperative Economics, 2020)
The last few years witnessed theoretical and practical contributions to the field of social innovation and social enterprise. However, analysis of the interplay between these two different realms is still limited. This article aims to fill some gaps in this respect. We deal with historical reconstruction of the concept of Social Enterprise and Social Innovation, and their conceptual premises. We consider the process of creation of social innovation in social enterprises. As members’ motivations, ownership rights and governance rules in social enterprises create a new relational context and new routines, which are germane to the production of social knowledge and deliberation, social innovation can be considered one of the main outcomes of this setting. Social motivations, collective action of a cooperative kind, multistakeholder governance and socialization of resources, and their interplay are singled out as main drivers of innovation. Social innovation is seen as akin to novelty in social interaction, a non-standardized and non-standardizable outcome of the operation of this organizational form.
Keywords: Entreprise; Europe; Innovation sociale; Mise en valeur; Réservé UdeM